Inflammasome activation in infected macrophages drives COVID-19 pathology - Sefik, Esen; Qu, Rihao; Junqueira, Caroline; Kaffe, Eleanna; Mirza, Haris; Zhao, Jun; Brewer, J. Richard; Han, Ailin; Steach, Holly R.; Israelow, Benjamin; Blackburn, Holly N.; Velazquez, Sofia E.; et al. (Nature (London), 2022)
Severe COVID-19 is characterized by persistent lung inflammation, inflammatory cytokine production, viral RNA and a sustained interferon (IFN) response, all of which are recapitulated and required for pathology in the SARS-CoV-2-infected MISTRG6-hACE2 humanized mouse model of COVID-19, which has a human immune system 1 – 20 . Blocking either viral replication with remdesivir 21 – 23 or the downstream IFN-stimulated cascade with anti-IFNAR2 antibodies in vivo in the chronic stages of disease attenuates the overactive immune inflammatory response, especially inflammatory macrophages. Here we show that SARS-CoV-2 infection and replication in lung-resident human macrophages is a critical driver of disease. In response to infection mediated by CD16 and ACE2 receptors, human macrophages activate inflammasomes, release interleukin 1 (IL-1) and IL-18, and undergo pyroptosis, thereby contributing to the hyperinflammatory state of the lungs. Inflammasome activation and the accompanying inflammatory response are necessary for lung inflammation, as inhibition of the NLRP3 inflammasome pathway reverses chronic lung pathology. Notably, this blockade of inflammasome activation leads to the release of infectious virus by the infected macrophages. Thus, inflammasomes oppose host infection by SARS-CoV-2 through the production of inflammatory cytokines and suicide by pyroptosis to prevent a productive viral cycle. A new humanized mouse model for COVID-19 demonstrates SARS-CoV-2 infection and subsequent activation of inflammasomes in human macrophages as a critical driver of disease.